STUDIES ON GENETIC VARIABILTY FOR YIELD AND FIBRE QUALITY TRAITS IN UPLAND COTTON (Gossypium hirsutum L.) - M Divya; N. SABITHA; K. MOHAN VISHNUVARDHAN (The Journal of Research ANGRAU, 2023)
Thirty genotypes of cotton were studied to estimate genetic variability, heritability (broad sense) and genetic advance for 15 traits during kharif, 2022. Analysis of variance showed significant amount of variation among the genotypes for traits studied. PCV was greater than GCV for all the traits except days to 50% flowering. High PCV and GCV were recorded for number of monopodial branches, lint index, lint yield and ginning percentage. High heritability coupled with genetic advance as percent of mean was observed for number of monopodial branches, plant height, seed cotton yield, lint index, lint yield, ginning percentage and micronaire indicating preponderance of additive gene action and hence simple selection would be effective for the improvement of these traits.